2016
DOI: 10.1152/ajpendo.00087.2016
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CTRP1 disrupts glucose and lipid homeostasis

Abstract: C1q/TNF-related protein 1 (CTRP1) is a conserved plasma protein of the C1q family with notable metabolic and cardiovascular functions. We have previously shown that CTRP1 infusion lowers blood glucose and that transgenic mice with elevated circulating CTRP1 are protected from diet-induced obesity and insulin resistance. Here, we used a genetic loss-of-function mouse model to address the requirement of CTRP1 for metabolic homeostasis. Despite similar body weight, food intake, and energy expenditure, Ctrp1 knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 79 publications
4
76
0
Order By: Relevance
“…It is known that female mice on a C57BL/6 genetic background are much less susceptible to diet-induced obesity (75,76). Many studies (77), including our previous studies (54)(55)(56) and the present study, reinforce the importance of sex as a biologic variable that can influence the impact and phenotypic outcomes of a given genotype. Intriguingly, although our current study and previous findings (62) do not support a major role for myonectin in regulating glucose metabolism, recent reports suggest that circulating myonectin in human blood is correlated with insulin resistance, impaired glucose metabolism, and type 2 diabetes (60,61).…”
Section: Discussionsupporting
confidence: 67%
“…It is known that female mice on a C57BL/6 genetic background are much less susceptible to diet-induced obesity (75,76). Many studies (77), including our previous studies (54)(55)(56) and the present study, reinforce the importance of sex as a biologic variable that can influence the impact and phenotypic outcomes of a given genotype. Intriguingly, although our current study and previous findings (62) do not support a major role for myonectin in regulating glucose metabolism, recent reports suggest that circulating myonectin in human blood is correlated with insulin resistance, impaired glucose metabolism, and type 2 diabetes (60,61).…”
Section: Discussionsupporting
confidence: 67%
“…These data indicate that late‐onset renal hypertrophy in Ctrp1 ‐KO mice fed a control LFD is associated with aging and not overt renal injury (eg, diabetic nephropathy, renal fibrosis, and inflammation). We previously showed that Ctrp1 ‐KO mice fed an LFD also develop fatty liver . Although the link between liver steatosis and glomerular hypertrophy is unclear, we cannot rule out the possibility that kidney enlargement in aged CTRP1‐deficient animals is indirectly due to metabolic dysfunction in the liver.…”
Section: Discussionmentioning
confidence: 87%
“…7 In vivo studies using recombinant protein infusion or genetic gain-and loss-offunction mouse models have established CTRP1's role in regulating systemic glucose and lipid metabolism. 14,19,24 Correlative human studies also support a role for CTRP1 as an adipokine with cardio-metabolic function. Elevated plasma levels of CTRP1 are found in patients with type 2 diabetes and metabolic syndrome, [41][42][43][44][45] non-alcoholic fatty liver disease, 46 coronary artery and heart disease, 33,[47][48][49][50][51] and hypertension.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations